Crystalline silicon solar cell passivation layer, preparation method and application of crystalline silicon solar cell passivation layer in crystalline silicon solar cell
By using H+-containing organic or inorganic compounds to prepare an ultra-thin passivation layer, both passivation and conductivity in crystalline silicon solar cells are achieved, and the problems of conductivity without passivation and passivation without conductivity in the prior art are solved, thereby reducing production costs.
Patent Information
- Application Number
- CN202411874462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The passivation layer materials of existing crystalline silicon solar cells have contradictions of conductivity and non-passivation, and the preparation process is complicated and the cost is high.
An ultrathin passivation layer is prepared using H+-containing organic compounds and/or inorganic compounds, and the H+ passivation mechanism is used to achieve both passivation and conductivity.
The preparation of an ultra-thin passivation layer is realized, which can not only tunnel and conduct electricity but also interface passivation, solving the problems of non-passivation and non-passivation of electricity, and reducing production costs.
Smart Images

Figure HDA0005196596380000011 
Figure HDA0005196596380000012 
Figure HDA0005196596380000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a crystalline silicon solar cell passivation layer, a preparation method and an application thereof in the crystalline silicon solar cell. Background Art
[0002] Over the past 30 years, the global photovoltaic market has been dominated by crystalline silicon (c-Si) solar cells due to their overwhelming advantages in efficiency, cost, stability and safety, with a market share of >90% currently conservatively estimated. Despite the rapid progress of emerging photovoltaic devices such as perovskite, organic and CIGS solar cells, continuous process improvements and the development of new cell architectures have enabled crystalline silicon solar cells to remain the leading photovoltaic technology.
[0003] From the early aluminum back surface field (Aluminum BSF) cells, to the recently industrialized passivated emitter and back cell (PERC), and the future large-scale silicon heterojunction (SHJ) and interdigitated back contact cells (IBC or HJ-IBC), the power conversion efficiency (PCE) of crystalline silicon solar cells has been continuously improved. High-quality surface passivation strategies and carrier selective contacts have played a key role in improving their PCE. At present, the PCE of crystalline silicon solar cells based on HJ-IBC has reached 26.7%. The main problem in crystalline silicon solar cell devices is the recombination loss caused by interface (between functional layers or on the side caused by broken edges) defect states. Therefore, reasonable surface passivation technology must be used to reduce recombination losses and increase component power.
[0004] At present, the most widely used in the industry are SiO2, SiN x , Al2O3 and intrinsic hydrogenated amorphous silicon (a-Si:H(i)) as thin film materials for interface passivation, and achieved good results. However, the use of these materials also inevitably brings some problems, such as: 1. Although the passivation effect of the above materials is significant, their insulation leads to the obstruction of the carrier transport process of the device; 2. Their preparation process is usually very complicated and requires the use of high temperature and high vacuum equipment (such as atomic layer deposition ALD and plasma enhanced chemical vapor deposition PECVD, etc.), which undoubtedly increases the cost of device production.
[0005] In summary, the current passivation layer materials are either made of insulating materials, which have a certain passivation effect but are not conductive, which will affect the conductivity of the battery, or materials with conductive properties do not have a passivation effect. The contradiction between conductive materials not being passivated and passivated materials not being conductive cannot be reconciled. The process of preparing the passivation layer and the conductive layer in steps in the industry is relatively complicated and costly.
[0006] Moreover, since the thickness of the passivation film in the prior art is nearly 100nm, it cannot conduct electricity without small holes, and the battery cannot be established. Therefore, the current passivation layer needs to be provided with conductive small holes to meet the conductivity requirements of the battery, and the process is relatively complicated.
[0007] Therefore, the development of low-cost and simple passivation technology is of vital importance to the development of future clean energy. Summary of the invention
[0008] In view of this, the technical problem to be solved by the present invention is to provide a crystalline silicon solar cell passivation layer, a preparation method and application thereof in a crystalline silicon solar cell, wherein the crystalline silicon solar cell passivation layer has both passivation and conductive properties.
[0009] To achieve the above object, the present invention provides a crystalline silicon solar cell passivation layer, comprising: + Organic compounds and / or H + Inorganic compounds.
[0010] The present invention proposes H + Passivation mechanism, using H + Organic compounds and / or H + Ultra-thin passivation layers prepared by inorganic compounds are used to passivate the interface defects of crystalline silicon cells. + Compounds achieve H + The passivation layer has the tunneling conductivity of the ultra-thin molecular layer, and a passivation layer that is both conductive and passivating is prepared, which solves the contradiction of the existing interface film "conductive but not passivating, passivating but not conductive".
[0011] The present invention is directed to the above-mentioned H-containing + The type of compound is not particularly limited, as long as it can dissociate into hydrogen ions.
[0012] The H-containing + The organic compound includes, but is not limited to, one or more organic compounds containing carboxyl, sulfonic acid, sulfinic acid, sulfhydryl, amino, and imino groups. Preferably, it includes one or more of bis(trifluoromethanesulfonyl)imide [BisTS, molecular formula: (CF3SO2)2NH], formic acid (HCOOH), acetic acid (CH3COOH), oxalic acid, propionic acid, malonic acid, citric acid (C6H8O7), oxalic acid, benzoic acid, p-toluenesulfonic acid, tartaric acid, malic acid, citric acid, ascorbic acid, salicylic acid, caffeic acid, etc., and more preferably bis(trifluoromethanesulfonyl)imide.
[0013] The H-containing + Inorganic compounds include those that can dissociate H +The inorganic compound includes, but is not limited to, one or more of nitric acid, sulfuric acid, sulfurous acid, hydrofluoric acid, phosphoric acid, pyrophosphoric acid, hydrochloric acid, boric acid, iodic acid, periodic acid, and carbonic acid, and preferably includes one or more of HF, H3PO4, etc.
[0014] The H-containing + The concentration of the compound is preferably 1-10 mg / mL, more preferably 1-3 mg / mL, including but not limited to 1 mg / mL, 2 mg / mL or 3 mg / mL.
[0015] The H-containing + The pH value of the compound is preferably 3-4.
[0016] The thickness of the passivation layer of the crystalline silicon solar cell is only a few nanometers, and electrons can be transported through the tunneling effect, and the conductivity will not be affected by the passivation effect, thus realizing a single-layer functional film of "passivation and conductivity integration". Preferably, its thickness is 1 to 10 nm, and more preferably 1.4 to 1.5 nm.
[0017] The passivation layer of the crystalline silicon solar cell is a continuous nano-thin film, and there is no need to set through holes, gaps and other structures in the structure for improving the conductive performance.
[0018] The present invention provides a method for preparing the above-mentioned crystalline silicon solar cell passivation layer, comprising the following steps:
[0019] H + Organic compounds and / or H + A solution of an inorganic compound is coated to form a passivation layer for a crystalline silicon solar cell.
[0020] The above preparation method preferably comprises the following steps:
[0021] Clean the back of the silicon electrode to remove the surface oxide layer;
[0022] The back of the cleaned silicon electrode is coated with H + Organic compounds and / or H + A solution of an inorganic compound, after removing the solvent, forms a crystalline silicon solar cell passivation layer on the back of the silicon electrode.
[0023] In the above solution, the solvent is preferably deionized water or an alcohol substance.
[0024] The alcohol substance preferably includes one or more alcohol solvents well known to those skilled in the art, such as methanol, ethanol, isopropanol, etc.
[0025] In some specific embodiments of the present invention, the solvent is methanol, ethanol or isopropanol.
[0026] In some specific embodiments of the present invention, the solvent is a mixed solvent of methanol, ethanol and isopropanol.
[0027] The volume ratio of methanol, ethanol and isopropanol is preferably 17-23: 2-4: 0.8-1.2. In some specific embodiments of the present invention, the volume ratio of methanol, ethanol and isopropanol is 20:3:1.
[0028] In the present invention, alcohols such as methanol, ethanol or isopropanol can be used alone as solvents, or mixed to achieve the passivation effect. + Compounds, not solvents. The solution of mixing the above three is the best solution. The above ratio of methanol, ethanol and isopropanol is the optimal ratio for experimental batteries used in the laboratory, not just this ratio for passivation.
[0029] The present invention has no particular limitation on the specific method of the above coating, and it can be any coating method well known to those skilled in the art, including but not limited to one or more of spray coating, spin coating, scraper coating, etc.
[0030] The coating time should not be too long, preferably 20 to 40 seconds, more preferably 30 seconds.
[0031] In some specific embodiments of the present invention, the spin coating is preferably specifically:
[0032] Place the cleaned battery into the spin coating equipment and + The compound solution is dripped onto the back of the battery, and the spin coating device is started to form a BisTs passivation layer on the back of the silicon battery. The spin coating speed is preferably 3000-4000 r / min, more preferably 3500 r / min; the spin coating time is preferably 20-40s, more preferably 30s.
[0033] The passivation film obtained by the above spin coating method is relatively uniform.
[0034] In some specific embodiments of the present invention, the spin coating is preferably specifically:
[0035] Put the cleaned part of the battery into the spin coating equipment and start the rotation directly. After reaching the target speed, + The compound solution drips onto the back of the battery, and the solution is instantly thrown to the surroundings by centrifugal force to form a passivation layer.
[0036] The target rotation speed is preferably 3000 to 4000 r / min, more preferably 3500 r / min.
[0037] The above spin coating method can reduce the exposure time of the battery in the air and reduce oxidation.
[0038] In some specific embodiments of the present invention, the above-mentioned scraping is specifically:
[0039] Put the cleaned part of the battery into the scraping equipment, + The compound solution is dripped onto the back of the battery, and the scraper height is adjusted to scrape from left to right to form a passivation layer on the back of the battery.
[0040] The above method can directly adjust the thickness of the passivation film.
[0041] The present invention has no particular limitation on the method for removing the solvent, and the method may be an applicable method well known to those skilled in the art, including but not limited to natural air drying, oven drying, etc.
[0042] The back side of the silicon electrode and the back side of the battery mentioned above refer to the non-light-receiving side.
[0043] Based on this, the present invention also provides a method for simultaneously improving the passivation effect and the conductive performance of a crystalline silicon solar cell, comprising the following steps:
[0044] Clean the back of the silicon electrode to remove the surface oxide layer;
[0045] The back of the cleaned silicon electrode is coated with H + Organic compounds and / or H + Solutions of inorganic compounds to improve their passivation effect and conductive properties.
[0046] In some specific embodiments of the present invention, after the coating operation, the silicon electrode is dried to form a passivation layer, and then other components of the composite battery, including but not limited to anti-reflection layers, electrodes, conductive layers, etc., are formed, which are crystalline silicon solar cell components well known to those skilled in the art.
[0047] The invention provides a crystalline silicon solar cell. The back side of a silicon electrode is provided with the crystalline silicon solar cell passivation layer.
[0048] Preferably, the crystalline silicon solar cell comprises in sequence:
[0049] Electrode layer, anti-reflection layer, silicon electrode, passivation layer, and back electrode.
[0050] The present invention has no special limitation on the materials of the electrode layer, anti-reflection layer, silicon electrode, and back electrode, and they may be any suitable material known to those skilled in the art.
[0051] The electrode layer includes but is not limited to aluminum silver electrode (AgAl) and the like.
[0052] The anti-reflection layer includes but is not limited to a silicon nitride anti-reflection layer and the like.
[0053] The above silicon electrodes include but are not limited to composite electrodes of P-type silicon electrodes and N-type silicon electrodes.
[0054] The back electrode mentioned above includes but is not limited to a silver electrode and the like.
[0055] Preferably, in the present invention, a conductive layer is further provided between the passivation layer and the back electrode of the crystalline silicon solar cell.
[0056] The provision of the above conductive layer can further improve the conductivity of the battery.
[0057] The present invention has no special limitation on the material of the conductive layer, and it can be a conductive layer well known to those skilled in the art, including but not limited to molybdenum oxide conductive coating, etc.
[0058] The thickness of the conductive layer is preferably 1-10 nm, more preferably 1.4-1.5 nm.
[0059] The silicon solar cell prepared by the present invention can realize interface passivation and selective transmission of carriers.
[0060] In some specific embodiments, the specific device structure of the silicon solar cell is as follows: Figure 1 shown.
[0061] Compared with the prior art, the present invention provides a crystalline silicon solar cell passivation layer, comprising H + Organic compounds and / or H + Inorganic compounds.
[0062] The present invention first discovered H + It has a passivation effect and is applied to the interface passivation of crystalline silicon cells to obtain the following beneficial effects:
[0063] 1. The thickness of the passivation layer is only a few nanometers, which is about 1 / 20 of the thickness of the current market. It has excellent interface passivation effect and conductive properties, and can achieve both tunneling conductivity and interface passivation. It does not require the setting of small holes for conductivity, which makes it possible to produce silicon solar cells at low cost.
[0064] 2. The passivation film can be prepared by the solution method, which no longer requires high-temperature and high-vacuum equipment, greatly simplifies the production process, further reduces production costs, and is green and environmentally friendly, occupies a small area, and has greater universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 Schematic diagram of the new crystalline silicon solar cell structure using bisTS as an ultra-thin passivation layer;
[0066] Figure 2 The JV curve of a new type of crystalline silicon cell prepared by spin coating passivation method with bisTS as an ultra-thin passivation layer in a p-type cell;
[0067] Figure 3The JV curve of a new type of crystalline silicon cell prepared by the fly-away passivation method using bisTS as an ultra-thin passivation layer on a p-type cell;
[0068] Figure 4 The JV curve of a new type of crystalline silicon cell prepared by the blade coating passivation method using bisTS as an ultra-thin passivation layer on a p-type cell;
[0069] Figure 5 The JV curve of a new type of crystalline silicon cell prepared by spin coating passivation method with bisTS as an ultra-thin passivation layer in a p-type cell;
[0070] Figure 6 This is a graph tracking the change of minority carrier lifetime over time. DETAILED DESCRIPTION
[0071] In order to further illustrate the present invention, the crystalline silicon solar cell passivation layer, the preparation method and the application thereof in the crystalline silicon solar cell provided by the present invention are described in detail below in conjunction with the embodiments.
[0072] Example 1
[0073] The back of the complete PERC cell was polished to expose the silicon cell surface, and then it was pickled with HF acid to remove the oxide layer formed on the silicon surface. Some of the cells were placed in a spin coating device, and 200 μL of BisTs solution was aspirated by a pipette and dropped onto the back of the cell. The spin coating device was started with a spin coating speed of 3500 r / min and a spin coating time of 30 s to form a BisTs passivation layer on the back of the silicon cell with a thickness of 1.41 nm.
[0074] In the BisTs solution, the solvent is a mixed solvent of methanol, anhydrous ethanol, and isopropanol, the solution volume ratio is 20:3:1, and the BisTs concentration is 2 mg / mL.
[0075] The passivation film obtained by spin coating is more uniform.
[0076] Assemble the battery, the structure is as follows Figure 1 shown. Figure 1 In the figure, the left figure is a schematic diagram of the structure, and the right figure is an enlarged schematic diagram of point A in the left figure.
[0077] IV test was carried out, and the battery without BisTs passivation layer was used as control. The results are as follows Figure 2 As shown. It can be seen that the current remains unchanged and there is no downward trend, but the open circuit voltage, fill factor, and conversion efficiency are significantly improved, and the final conversion efficiency is increased by 0.7%. It can be concluded that this passivation layer has a significant passivation effect, but has no effect on conductivity.
[0078] Example 2
[0079] The back of the complete PERC cell is polished to expose the silicon cell surface, and then it is pickled with HF acid to remove the oxide layer formed on the silicon surface. Some cells are placed in the spin coating equipment and the rotation is directly turned on. When the speed reaches 3500r / min, the BisTs solution is dripped on it. The solution will be instantly thrown to the surroundings by centrifugal force to form a passivation layer with a thickness of 1.41nm.
[0080] In the BisTs solution, the solvent was the same as in Example 1, and the BisTs concentration was 2 mg / mL.
[0081] The advantage of this method is that it reduces the exposure time of the battery in the air and reduces oxidation.
[0082] Assemble the battery, the structure is as follows Figure 1 shown.
[0083] IV test was carried out, and the battery without BisTs passivation layer was used as control. The results are as follows Figure 3 As shown in the figure, it can be seen that the open circuit voltage and fill factor are significantly improved, and the final conversion efficiency is increased by 0.59%. The passivation layer has a significant passivation effect and has no effect on the conductive properties.
[0084] Example 3
[0085] The back of the complete PERC cell is polished to expose the silicon cell surface, and then it is pickled with HF acid to remove the oxide layer formed on the silicon surface. Some cells are placed on the scraping equipment, and the BisTs solution is dripped onto the cell surface. The scraper height is adjusted and scraped from left to right to form a passivation layer on the back of the cell with a thickness of 1.41nm.
[0086] In the BisTs solution, the solvent was the same as in Example 1, and the BisTs concentration was 2 mg / mL.
[0087] The advantage of this method is that the thickness of the passivation film can be directly adjusted.
[0088] Assemble the battery, the structure is as follows Figure 1 shown.
[0089] IV test was carried out, and the battery without BisTs passivation layer was used as control. The results are as follows Figure 4 As shown in the figure, it can be seen that the open circuit voltage and fill factor are significantly improved, and the final conversion efficiency is increased by 0.8%. The passivation layer has a significant passivation effect and has no effect on the conductive properties.
[0090] Example 4
[0091] The back of the TOPCon battery was polished to expose the surface of the silicon battery, and then it was pickled with HF acid to remove the oxide layer formed on the silicon surface. Some of the batteries were placed in a spin coating device, and 200 μL of BisTs solution was aspirated by a pipette and dropped onto the back of the battery. The spin coating device was started with a spin coating speed of 3500 r / min and a spin coating time of 30 s to form a BisTs passivation layer on the back of the silicon battery with a thickness of 1.41 nm.
[0092] In the BisTs solution, the solvent was the same as in Example 1, and the BisTs concentration was 2 mg / mL.
[0093] The assembled battery was used as a control, and the IV test was performed with the battery without BisTs passivation layer as the control. The results are as follows Figure 5 As shown in the figure, it can be seen that the open circuit voltage and fill factor are significantly improved, and the final conversion efficiency is increased by 1.45%. The passivation layer has a significant passivation effect and has no effect on the conductive properties.
[0094] It can be seen from the above embodiments that no matter which passivation method is used and no matter on which battery the passivation is performed, the open circuit voltage and fill factor are advantageous when the passivation method provided by the present invention is used, the conversion efficiency loss is lower than that of the control group, and the stability is better.
[0095] Example 5 Comparison of passivation effects of different acids
[0096] Select 3000-5000Ω double-polished silicon wafers and pickle them to remove the surface oxide layer. Then put the silicon wafer on the glue spreader and use a pipette to suck 350μL of passivation liquid droplets onto the silicon wafer. Turn on the glue spreader and start spin coating at a speed of 3500r / min. After 30s, spin coating is completed on one piece of silicon wafer. Then, the reverse side is spin coated in the same way for double-sided passivation. The thickness of the passivation layer is 1.5nm. After spin coating, put it on the Sinton equipment for testing to obtain the minority carrier lifetime (i.e., passivation effect).
[0097] The passivation solutions are hydrofluoric acid (HF, concentration 5%); phosphoric acid (H3PO4, concentration 5%); [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz, concentration 2 mg / mL) + KOH (concentration 5%); polyvinylcarbazole (PVK, concentration 5%).
[0098] The solvent is the same as in Example 1.
[0099] The results are as follows Figure 6 shown.
[0100] Depend on Figure 6 It can be seen that both hydrofluoric acid and phosphoric acid have a passivation effect, wherein the minority carrier lifetime of hydrofluoric acid passivation is about 0.2 ms, and the minority carrier lifetime of phosphoric acid passivation is about 1.0 ms.
[0101] Neutralize the acidic 2PACz+KOH group and the H + The PVK group has no passivating effect.
[0102] This proves that H + It plays a key role in passivation.
[0103] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A crystalline silicon solar cell passivation layer comprising H + Organic compounds and / or H + Inorganic compounds.
2. The crystalline silicon solar cell passivation layer according to claim 1, characterized in that: The H-containing + The organic compound includes one or more organic compounds containing carboxyl group, sulfonic acid group, sulfinic acid group, mercapto group, amino group, and imino group; The H-containing + Inorganic compounds include those that can dissociate H + of inorganic compounds.
3. The crystalline silicon solar cell passivation layer according to claim 2, characterized in that: The H-containing + The organic compound includes one or more of bis(trifluoromethanesulfonyl)imide, formic acid, acetic acid, oxalic acid, propionic acid, malonic acid, citric acid, oxalic acid, benzoic acid, p-toluenesulfonic acid, tartaric acid, malic acid, citric acid, ascorbic acid, salicylic acid, and caffeic acid; The H-containing + The inorganic compound includes one or more of nitric acid, sulfuric acid, sulfurous acid, hydrofluoric acid, phosphoric acid, pyrophosphoric acid, hydrochloric acid, boric acid, iodic acid, periodic acid, and carbonic acid.
4. The crystalline silicon solar cell passivation layer according to claim 1, characterized in that: The passivation layer of the crystalline silicon solar cell is a continuous nano film; The thickness of the passivation layer of the crystalline silicon solar cell is 1-10 nm.
5. The method for preparing a passivation layer of a crystalline silicon solar cell according to any one of claims 1 to 4, comprising the following steps: H + Organic compounds and / or H + A solution of an inorganic compound is coated to form a passivation layer for a crystalline silicon solar cell.
6. The preparation method according to claim 5, characterized in that: The coating is one or more of spray coating, spin coating and blade coating.
7. The preparation method according to claim 5, characterized in that: The following steps are involved: Clean the back of the silicon electrode to remove the surface oxide layer; The back of the cleaned silicon electrode is coated with H + Organic compounds and / or H + A solution of an inorganic compound, after removing the solvent, forms a crystalline silicon solar cell passivation layer on the back of the silicon electrode.
8. A crystalline silicon solar cell, wherein the back side of a silicon electrode is provided with the crystalline silicon solar cell passivation layer according to any one of claims 1 to 4.
9. The crystalline silicon solar cell according to claim 8, characterized in that: Including in order: Electrode layer, anti-reflection layer, silicon electrode, passivation layer, and back electrode.
10. The crystalline silicon solar cell according to claim 9, characterized in that: A conductive layer is also arranged between the passivation layer and the back electrode.